A Cost-effectiveness Analysis of an Adjuvanted Subunit Vaccine for the Prevention of Herpes Zoster and Post-herpetic Neuralgia. (8th May 2019) - Carpenter, Christopher F; Aljassem, Annas; Stassinopoulos, Jerry; Pisacreta, Giovanni; Hutton, David
Abstract: Background: Herpes zoster (HZ) develops in up to 50% of unvaccinated individuals, accounting for >1 million cases annually in the United States. A live attenuated HZ vaccine (LAV) is Food and Drug Administration approved for those age 50 years or older, though Advisory Committee on Immunization Practices recommendations are only for those age 60 years or older. LAV efficacy is 70% for persons 50–59 years of age, with lower efficacy in older adults. A new 2-dose adjuvanted subunit vaccine (SUV) has >95% efficacy in persons 50–69 years of age and remains 90% efficacious in persons vaccinated at age 70 years. Methods: To estimate the relative cost-effectiveness of SUV, LAV, and no vaccination (NoV) strategies, a Markov model was developed based on published data on vaccine efficacy, durability of protection, quality of life, resource utilization, costs, and disease epidemiology. The perspective was US societal, and the cycle length was 1 year with a lifelong time horizon. SUV efficacy was estimated to wane at the same rate as LAV. Outcomes evaluated included lifetime costs, discounted life expectancy, and incremental cost-effectiveness ratios (ICERs). Results: For individuals vaccinated at age 50 years, the ICER for LAV vs NoV was 118 535 per quality-adjusted life-year (QALY); at age 60 years, the ICER dropped to 42 712/QALY. SUV was more expensive but had better ICERs than LAV. At age 50, the ICER was 91 156/QALY, and it dropped to 19 300/QALY at age 60. Conclusions: Vaccination with SUV was more cost-effective than LAV in all age groups studied. Vaccination with SUV at age 50 years appears cost-effective, with an ICER <100 000/QALY. Abstract : This manuscript describes a cost-effectiveness analysis utilizing a Markov decision model that demonstrates vaccination with the two-dose adjuvanted subunit herpes zoster vaccine, given current pricing, offers very good value in comparison to the live attenuated herpes zoster vaccine or no vaccination strategy. Even at higher prices, faster waning rates, and poorer adherence to the second dose, our model suggests the subunit vaccine remains cost-effective at a willingness-to-pay threshold of 100, 000 per quality-adjusted life-year.